The bad sleep well = Warui yatsu hodo yoku nemuru - Satō, Masaru 1928-1999 (The Criterion Coll., 2006)
A young executive hunts down his father's killer. A tale about corruption in the boardrooms of postwar corporate Japan as seen through the rising executive eyes.
Aspect ratio 2.35:1, 16:9 widescreen. - New, restored high-definition digital transfer
Orig.: Japan 1960
Enth. a 33-minute documentary on the making of "The Bad Sleep Well" ; new essays by film critic Chuck Stephens and director Michael Almereyda
Keywords: Corporations -- Corrupt practices -- Japan -- Drama; Murder -- Investigation -- Japan -- Drama; Film; Feature films; Fiction films; Foreign films; Thrillers (Motion pictures); Thriller - Feature